2020
DOI: 10.3389/fpubh.2020.597897
|View full text |Cite
|
Sign up to set email alerts
|

Medical Students' Awareness of Smell Loss as a Predictor for Coronavirus Disease 2019

Abstract: Background: Anosmia has been reported as an early presentation of coronavirus disease 2019 (COVID-19). However, the pathophysiological mechanism of olfactory dysfunction is still unclear.Aim: The aim of this study to evaluate the knowledge regarding common symptoms, anosmia, treatment options, and PPE among medical students in three different universities of Saudi Arabia.Methods: This cross-sectional survey conducted among medical students in Saudi Arabia. Google Forms was used to create the survey. The questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…< 0.001), and taste disorder (0.317 vs. 0.115%; Sig . < 0.001) among COVID-19 vaccinees is the increased public awareness of taste dysfunction as one of the characteristic symptoms of COVID-19 infection ( 17 , 18 ). Our hypothesis can be supported by the overall reporting prevalence of taste disorders during the COVID-19 pandemic period compared to the pre-pandemic years.…”
Section: Discussionmentioning
confidence: 99%
“…< 0.001), and taste disorder (0.317 vs. 0.115%; Sig . < 0.001) among COVID-19 vaccinees is the increased public awareness of taste dysfunction as one of the characteristic symptoms of COVID-19 infection ( 17 , 18 ). Our hypothesis can be supported by the overall reporting prevalence of taste disorders during the COVID-19 pandemic period compared to the pre-pandemic years.…”
Section: Discussionmentioning
confidence: 99%
“… Alsukah/Dec 2020 33 Individuals’ Self-Reactions Toward COVID-19 Pandemic in Relation to the Awareness of the Disease and Psychological Hardiness in Saudi Arabia 1272 participants Online questionnaire A high level of COVID-19 awareness (91.50%) was identified among studied Saudi participants. Aljameel/Dec 2020 34 A Sentiment Analysis Approach to Predict an Individual’s Awareness of the Precautionary Procedures to Prevent COVID-19 Outbreaks in Saudi Arabia. 242,525 Arabic tweets A dataset of Arabic COVID-19-related tweets The awareness prediction model showed that the south region observed the highest level of awareness towards COVID-19 containment measures, whereas the middle region was the least.…”
Section: The Searched Outcomesmentioning
confidence: 99%
“…Unlike other vaccines, COVID‐19 vaccines were associated with a significantly higher frequency of taste‐related SEs in the United States. Several hypotheses can be proposed to explain this finding: (i) the increased public awareness of taste disorders had probably increased during the COVID‐19 pandemic due to utilizing taste disorders in differential diagnosis and case triage, (ii) the increased possibility of breakthrough infections that could be associated with taste disorders as clinical complications, and (iii) suffering from taste disorders as a result of long COVID‐19 39–41 …”
Section: Discussionmentioning
confidence: 99%